DIFFERENCE EQUATION FOR AUSTRALIAN SHEEP BLOWFLIES GROWTH - Gisbtarani, J I; Huda, M N; Setiyaningsih, H; Solikhatun, Solikhatun (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
The population of Australian sheep blowflies, Lucilia cuprina, in Australia is of concern to many researchers because it causes several problems. These problems occur in the sheep industry where there is a term "flystrike" in the industry. Flystrike is a fly attack on sheep that causes myiasis on the sheep's skin, affecting the quality and quantity of wool. In the worst cases, the sheep may die if not treated. This issue has attracted researcher to conduct a population control study of fly growth to suppress flystrike in the Australian sheep industry. In this paper, fly growth will be approached using a difference equation to better represent the industry’s situation. This equation will be analyzed using its approximate solution that is obtained through linearization of perturbation method, Cardano’s formula, and Galois solution’s method. By studying fly growth, Australian sheep farmers may find it easier to handle and prevent fly infestations using the solution.